Design and Preparation of Molecularly Imprinted Membranes for Selective Separation of Acteoside - Zhao, Xiaobin; Cheng, Yun; Xu, Helin; Hao, Yanyan; Lv, Yin; Li, Xueqin (Frontiers in Chemistry, 2020)
A novel class of molecularly imprinted membranes (MIMs) was designed and synthetised using PVDF membranes as substrates for high permselective separation and fast recognition of acteoside (ACT). The effects of the different functional monomers, the amounts of functional monomers, crosslinking agent and initiator on the separation properties of MIMs were investigated. Furthermore, adsorption ability, permeation capacity and reusability of MIMs were discussed for ACT. The results indicated that MIM7 exhibited the optimal adsorption ability of 62.83 mg/g for ACT, and the selectivity factor (α) of MIM7 was up to 2.74 and its permeability factor (β) was greater than 2.66. Moreover, the adsorption capacities of MIM7 were still more than 88.57%of maximal adsorption amount after 5 cycles. Because ACT imprinted layer of MIMs had only recognition sites for ACT molecules, which recombined with the recognition sites in the membrane permeation experiment, and ACT molecules were hindered penetration. However, the analogues of echinacoside (ECH) successfully passed MIMs. It indicated that the hindered permeation mechanism played the main role in selective separation of ACT through MIMs. This work provides an important reference for the high permselective separation of natural products.